Stoneheart [compact disc, unabridged] - Fletcher, Charlie, 1960- (Fletcher, Charlie, 1960- Stoneheart trilogy, 2007)
When twelve-year-old George accidentally decapitates a stone statue in London, England, he falls into a parallel dimension where he must battle ancient "live" statues and solve a dangerous riddle.